Validasi Instrumen Angket Faktor-Faktor Penyebab Kesulitan Belajar Siswa SMA pada Materi Stoikiometri - Putri Meidilla Rahmi; Bali Yana Fitri (Lembaga Yasin AlSys, 2026)
Learning difficulties in stoichiometry are still widely experienced by senior high school students because the subject requires the integration of conceptual understanding of chemistry and mathematical calculation skills, while also serving as an important foundation for mastering subsequent chemistry topics. This condition indicates the need for an instrument capable of systematically and measurably identifying the factors that cause students’ learning difficulties. This study aimed to develop a valid questionnaire instrument to identify the factors causing senior high school students’ learning difficulties in stoichiometry. The study employed a research and development method based on DeVellis’s (2017) instrument development model. The development process comprised five stages: determining the construct to be measured, developing a pool of statement items, determining the measurement format, conducting expert reviews of the items, and considering the validation results. The content validity of the instrument was analyzed using Aiken’s V index involving five validators. The results showed that the developed instrument obtained a mean Aiken’s V value of 0.842 and was therefore considered to have adequate content validity. Of the initial 83 statement items, 31 items were retained after undergoing a selection and revision process based on feedback from the validators. This study concludes that the developed instrument is valid as an initial draft for identifying the factors causing students’ learning difficulties in stoichiometry. The instrument may serve as a basis for further research involving empirical validity and reliability testing before being used more widely.